Optimalisasi Biaya Dan Waktu Pada Usaha Kerajinan Kayu Hitam Di Sumber Urip Ebony Dengan Menggunakan Metode Hungarian - Maharani, M; Jaya, A I; Sahari, A (Program Studi Matematika, Universitas Tadulako, 2019)
ABSTRACTPalu as the Capital of Central Sulawesi province is known as one of the crafts made from ebony. Ebony woodcraft industry in Palu begin to increase with the establishment of several business ebony, one of them is Sumber Urip Ebony Store that not only as a shop to sell the crafts, but at the same time as a place to produce the ebony wood crafts . This store have 9 workers and already have an adequate means of production. This study aimed is to propose the hungarian method to solve multi-objective assignment by optimizing the cost and time of production. From the results of the study is obtained that the total cost of producing all kinds of crafts is Rp. 8,080,000, - with a total of 87 days. This indicates more efficient results when compared with the cost of Rp. 12.6 50.000, - with a total of 115 days at Sumber Urip Ebony Store.Keywords : Assignments of Workers, Hungarian Method, Multi-objective Assignment, Optimize.